Marsupial Genetics and Genomics 2010
DOI: 10.1007/978-90-481-9023-2_22
|View full text |Cite
|
Sign up to set email alerts
|

Marsupial Population and Conservation Genetics

Abstract: Recent technological advances have resulted in a dramatic renaissance of population genetics and its application to species ecology and conservation. This review summarizes the progress made in applying these new techniques, notably hypervariable genetic markers (microsatellite loci and mitochondrial control region), to the study of marsupials. Since 1990, population genetic studies have overwhelmingly been of marsupial species from eastern and southern Australia, largely focusing on threatened species or thos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 181 publications
1
7
0
Order By: Relevance
“…These values were comparatively lower than previously reported for other Antechinus (Appendix S6). While variation in sample size can influence these values, it is notable that genetic variation in both species was similar to averages reported in the last review of marsupial population genetic diversity (Eldridge, 2010), in which the majority of studied taxa were listed as threatened species. For instance, levels of genetic variation found in the current study were similar to that found for well-connected populations of two threatened marsupials, the Vulnerable brush-tailed rock-wallaby, Petrogale penicillata (Hazlitt, Goldizen, & Eldridge, 2006) and mainland populations of the Endangered northern quoll, Dasyurus hallucatus (Cardoso et al, 2009).…”
Section: Genetic Differentiation and Variation Between A Mysticussupporting
confidence: 80%
“…These values were comparatively lower than previously reported for other Antechinus (Appendix S6). While variation in sample size can influence these values, it is notable that genetic variation in both species was similar to averages reported in the last review of marsupial population genetic diversity (Eldridge, 2010), in which the majority of studied taxa were listed as threatened species. For instance, levels of genetic variation found in the current study were similar to that found for well-connected populations of two threatened marsupials, the Vulnerable brush-tailed rock-wallaby, Petrogale penicillata (Hazlitt, Goldizen, & Eldridge, 2006) and mainland populations of the Endangered northern quoll, Dasyurus hallucatus (Cardoso et al, 2009).…”
Section: Genetic Differentiation and Variation Between A Mysticussupporting
confidence: 80%
“…For autosomal microsatellites the levels of diversity ( A , He ) are amongst the highest yet reported in marsupials [2]. A remarkably high number of Y haplotypes were also detected in the Kangaroo Island population (Table 4, [27]), compared to other tammar populations, a more widespread and abundant macropodid (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…The study of Australia’s unique marsupial fauna, continues to offer valuable insights into multiple fields including evolutionary genetics [ 1 ] and conservation biology [ 2 ]. The tammar wallaby ( Notamacropus eugenii ) (see [ 3 , 4 ] regarding the change of genus from Macropus ) is one of the most intensively studied marsupials, and has become a significant model species for reproductive, developmental, physiological, immunological, ecological and genetic research (see [ 1 , 5 , 6 – 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…NC_003322, KY996502 and KY996500, respectively). However, as marsupial population genetic studies have mainly utilised microsatellites and the control region [32][33][34][35], the number of cytb sequences available on GenBank is not extensive.…”
Section: Sequence Alignment Primer Design and Evaluationmentioning
confidence: 99%